2013
DOI: 10.1155/2013/798403
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic versus Radiation-Associated Angiosarcoma: A Comparative Clinicopathologic and Molecular Analysis of 48 Cases

Abstract: Angiosarcomas are aggressive tumors of vascular endothelial origin, occurring sporadically or in association with prior radiotherapy. We compared clinicopathologic and biologic features of sporadic angiosarcomas (SA) and radiation-associated angiosarcomas (RAA). Methods. From a University of Michigan institutional database, 37 SA and 11 RAA were identified. Tissue microarrays were stained for p53, Ki-67, and hTERT. DNA was evaluated for TP53 and ATM mutations. Results. Mean latency between radiotherapy and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…We did not find any specific toxin or drug exposure in review of HSVN patient history. MYC amplification has been established in some primary (non–radiation-associated) cutaneous ASs [1], and a subset of nonhepatic, sporadic ASs has abnormal p53/ TP53 [26]; we found IHC evidence to support similar changes in hepatic AS but no IHC or molecular evidence of a MYC or TP53 abnormality in HSVN.…”
Section: Discussionmentioning
confidence: 50%
“…We did not find any specific toxin or drug exposure in review of HSVN patient history. MYC amplification has been established in some primary (non–radiation-associated) cutaneous ASs [1], and a subset of nonhepatic, sporadic ASs has abnormal p53/ TP53 [26]; we found IHC evidence to support similar changes in hepatic AS but no IHC or molecular evidence of a MYC or TP53 abnormality in HSVN.…”
Section: Discussionmentioning
confidence: 50%
“…Vorburger et al demonstrated a shorter mean latency period (between initiation of radiation therapy and development of AS) of 7.6 years for breast RAA, compared with 20.9 years for RAA arising in other anatomic sites 7. A study by Hung et al comparing RAA and sporadic AS of the breast showed that 80% of RAA were cutaneous in origin, compared with sporadic AS, of which 80% demonstrated parenchymal origin 8. Interestingly, there appears to be no difference in survival between sporadic AS and RAA of the breast 7 9…”
Section: As Variants and Their Incidencementioning
confidence: 99%
“…Mutations of the TP53 gene in angiosarcomas were examined in some studies. Although their results varied, TP53 gene mutations were found in 4–52% of cases, and overexpression of p53 was immunohistochemically detected in 20–49% of cases …”
Section: Discussionmentioning
confidence: 99%
“…Although their results varied, TP53 gene mutations were found in 4-52% of cases, and overexpression of p53 was immunohistochemically detected in 20-49% of cases. [16][17][18] In this case, undifferentiated sarcomatoid cells expressing pan-cytokeratin were detected in the transitional zone between HCC and mesenchymal cells, indicating that the sarcomatoid cells might have been derived from carcinoma cells via a metaplastic or dedifferentiation process. The tumor showed strong and diffuse expression of p53 protein in the nucleus of angiosarcomatoid cells in contrast to lower levels of expression in undifferentiated sarcomatoid and carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%